2023
DOI: 10.1080/22221751.2023.2169198
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection-induced immunity reduces rates of reinfection and hospitalization caused by the Delta or Omicron variants

Abstract: During a pandemic, effective vaccines are typically in short supply, particularly at onset intervals when the wave is accelerating. We conducted an observational, retrospective analysis of aggregated data from all patients who tested positive for SARS-CoV-2 during the waves caused by the Delta and Omicron variants, stratified based on their known previous infection and vaccination status, throughout the University of Texas Medical Branch (UTMB) network. Next, the immunity statuses within each medical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
1
8
0
1
Order By: Relevance
“…Recent studies reported that SARS-CoV-2 infection-induced immunity reduced rates of reinfection and hospitalization caused by later variants [ 7 ]. It is not clear how long such immunity may last but such infection-induced-immunity can supplement vaccine-induced-immunity, by forming the “hybrid immunity” as being described in recent literature [ 8 ].…”
Section: Chance For New Variants To Be Created Dramatically Different...mentioning
confidence: 99%
“…Recent studies reported that SARS-CoV-2 infection-induced immunity reduced rates of reinfection and hospitalization caused by later variants [ 7 ]. It is not clear how long such immunity may last but such infection-induced-immunity can supplement vaccine-induced-immunity, by forming the “hybrid immunity” as being described in recent literature [ 8 ].…”
Section: Chance For New Variants To Be Created Dramatically Different...mentioning
confidence: 99%
“…The mean pooled effectiveness from past infection was greater than 78% against severe reinfection (hospitalization and death) for all variants, including Omicron BA.1 36 . Both infection‐induced and hybrid immunities could reduce the rates of hospitalizations, intensive care unit admissions, and deaths associated with reinfection, compared to those without pre‐existing immunity 37 …”
Section: The Severity Of Reinfections Compared With Initial Infectionsmentioning
confidence: 94%
“…36 Both infection-induced and hybrid immunities could reduce the rates of hospitalizations, intensive care unit admissions, and deaths associated with reinfection, compared to those without pre-existing immunity. 37 The initial infection or vaccination produces protective antibodies, which should reduce the probability of severe symptoms upon reinfection. Surveillance data from January 2020 to May 2021 in the United Kingdom during the early stage of the SARS-CoV-2 epidemic showed a 61% lower mortality rate for reinfection compared to primary infection.…”
Section: The Severity Of Reinfections Compared With Initial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the combination of natural infection and vaccination has significantly increased global immunity to SARS-CoV-2 as observed in two different reviews [11,12]. The latest data indicates that the decreasing numbers of deaths and hospitalizations can be attributed, in large part, to the high levels of population immunity against SARS-CoV-2 [13]. Similarly, systematic efforts to control Mpox have led to a significant reduction in new cases over the past three months.…”
Section: The Successesmentioning
confidence: 99%